2022
DOI: 10.1038/s41598-022-25426-5
|View full text |Cite
|
Sign up to set email alerts
|

Abstractness emerges progressively over the second year of life

Abstract: words, terms not referring to here and now, are acquired slowly in infancy. They are difficult to acquire as they are more detached from sensory modalities than concrete words. Recent theories propose that, because of their complexity, other people are pivotal for abstract concepts’ acquisition and use. Eight children (4 girls) and their mothers were observed longitudinally and extensively from 12 to 24 months of age. Video recordings of mother-infant free play with toys were done every two weeks in a laborato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 83 publications
0
3
0
Order By: Relevance
“…Infants start to understand the first abstract words at around 10 and 14 months when they develop social abilities such as engaging in joint action and following others' gaze (Bergelson, Swingley, 2013). As to word production, abstract concepts are hard words and children start to use them quite late (Bellagamba et al, 2022). To acquire them, previous linguistic knowledge (linguistic acquisition modality) and the support of others are needed (social metacognition, Villani et al, 2019;Mazzuca et al, 2022).…”
Section: Abstract Concepts and Languagementioning
confidence: 99%
“…Infants start to understand the first abstract words at around 10 and 14 months when they develop social abilities such as engaging in joint action and following others' gaze (Bergelson, Swingley, 2013). As to word production, abstract concepts are hard words and children start to use them quite late (Bellagamba et al, 2022). To acquire them, previous linguistic knowledge (linguistic acquisition modality) and the support of others are needed (social metacognition, Villani et al, 2019;Mazzuca et al, 2022).…”
Section: Abstract Concepts and Languagementioning
confidence: 99%
“…New clues about potential mechanisms have been provided by recent studies. For example, a recent study of eight infants over the second year of life found there was incremental growth of abstract words and that social interactions with caregivers were instrumental to the learning of abstract words (Bellagamba et al, 2022). In addition, Nook et al (2020) examined the development of emotion concepts and found that there was a shift from understanding emotions within an external, concrete situation to understanding in terms of internalized concepts.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…New clues about potential mechanisms have been provided by recent studies. For example, a recent study of eight infants over the second year of life found there was incremental growth of abstract words and that social interactions with caregivers were instrumental to the learning of abstract words (Bellagamba et al, 2022). In addition, Nook et al (2020) examined the development of emotion concepts and found DEVELOPING ABSTRACT WORD MEANING 18 that there was a shift from understanding emotions within an external, concrete situation to understanding in terms of internalized concepts.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%